2006
DOI: 10.1103/physrevc.73.024612
|View full text |Cite
|
Sign up to set email alerts
|

Reactions in theB8andLi8compound systems

Abstract: Calculations are reported for reactions in the 8 B and 8 Li compound systems with the recoil corrected continuum shell model. Comparison with observed structure indicates that the spin-orbit component of the M3Y interaction must be modified near the middle of the p shell. Calculations are performed with three spin-orbit strengths. The prediction for 7 Be(p, γ ) 8 B, based on this model and available data, is that S 17 (0) equals 21.63 eV b and S 17 (20) 21.02 eV b. Calculations for 7 Li(n, γ ) 8 Li indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 31 publications
(67 reference statements)
2
31
0
Order By: Relevance
“…Csoto [13] predicted a 1 + state at E x % 1.4 MeV, which was though not observed in experiments [10]. Very recently, Halderson [14] suggested that the known 3 + state is part of a group of three states which includes a 0 + and a 1 + state possibly energetically degenerate with the 3 + . We here report on first results from an elastic and inelastic scattering experiment using a radioactive 7 Be beam impinging on thin polyethylene targets.…”
Section: Be Scattering Experiments At Hribfmentioning
confidence: 96%
“…Csoto [13] predicted a 1 + state at E x % 1.4 MeV, which was though not observed in experiments [10]. Very recently, Halderson [14] suggested that the known 3 + state is part of a group of three states which includes a 0 + and a 1 + state possibly energetically degenerate with the 3 + . We here report on first results from an elastic and inelastic scattering experiment using a radioactive 7 Be beam impinging on thin polyethylene targets.…”
Section: Be Scattering Experiments At Hribfmentioning
confidence: 96%
“…(See also Refs. [25,26] for similar results using methods related to the "traditional" shell model. )…”
Section: Introduction a Motivationmentioning
confidence: 94%
“…In addition to the models described in the experimental papers [12,15,16], many theoretical calculations have described the available data (see for example [41][42][43][44][45][46][47][48]). …”
Section: Comparison To Theorymentioning
confidence: 99%